THE NEW METHODOLOGY OF NEGOTIATING WITH THE CANDIDATE COUNTRIES IN THE CONTEXT OF MACRON’S RESHAPING OF EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2020)
The enlargement policy of the European Union is known to be one of its best policies, as it has united a continent, stretched the single market and the common policies, thus conforming many aspects of economic and social life in the European countries. The Western Balkan has become, since the dissolution of ex-Yugoslavia, a very important geopolitical region, known also to be the soft belly of Europe. Thessaloniki Summit, held back in 2003, stamped the European perspective on the Western Balkans and declared it as a near future for the region. Since the entering of Romania and Bulgaria in 2007, it has tightened the negotiation rules, pointing out that the Rule of Law is the most important principle and measure of success for the candidate countries. Now, almost seventeen years from the Thessaloniki moment, the EU has stopped the enlargement policy, as the Member States have not found common ground as to open negotiation talks with North Macedonia and Albania. It seems fair to say that the enlargement does not have anymore its geopolitical relevance. It seems that the EU, due to the financial crisis in 2008, and then the migration crisis that followed, has lost its capacity to absorb new member states. However, France, which is starting to play a more central role in the European centerfield, is proposing a new approach to the Western Balkans, presenting a new methodology. The main point of the French proposal is to gradually include candidate countries in the club, by making them achieve certain rights by passing through various phases, seven of them exactly. One of the most important aspects is also the fact that the candidate countries would have access to structural funds, which they do not have today. However, the French proposal isn’t peacefully accepted yet, as many countries have objected. From a geopolitical standpoint, how is this affecting Europe and how the Western Balkan region? Are Macron’s proposals going to slow down the reform processes, thus endangering all that has been accomplished so far? In terms of common foreign and security policy, and the external action of the EU, can the new methodology play a role? In the context where the EU has to play a more active role in the neighbouring regions, it needs stability and more strength. Will Macron deliver just what is needed or will he turn the situation upside down? Analytical and comparative methods will be dominantly relied upon throughout the paper allowing the author i.e. to draw the arguments supporting or challenging the above mentioned dilemmas and issues raised.